Bioengineered nanovesicles for efficient siRNA delivery through ligand-receptor-mediated and enzyme-controlled membrane fusion - Lele Cui; Yongsheng Cui; Jing Liu; Wei Li; Mengdan Wu; Xiawei Wei; Ying Lai; Peng Mi (Nature Communications)
Abstract A major obstacle in knocking down oncogenes for tumor therapy is the efficient delivery of siRNA into the cytosolic spaces of cancer cells. Here, we genetically bioengineer biomimetic nanovesicles with tumor-recognition and enzyme-controlled membrane fusion functions for efficiently delivering small interfering RNA into cancer cells towards gene silencing tumor therapy. The siRNA@eS-BNVs are formulated by encapsulating siRNA inside the core and coating with genetically engineered HEK293TACE2- cell membranes encoded with functional S protein, which can recognize cancer cells and initiate membrane fusion when triggered by the enzyme. The siRNA@eS-BNVs demonstrate better efficacy for cytosolic siRNA delivery and RNA interference than conventional formulations. By intravenous injection, siRNA@eS-BNVs are highly accumulated in tumors and potently inhibited tumor and lung metastasis by simultaneously silencing the epidermal growth factor receptor gene in vivo. The cancer cell-targeting and enzyme-activatable nanovesicles provide a valuable strategy for effective and precise drug delivery.